Challenges in the sustainability of Libyan agriculture: opportunities for the Libyan seed system - Lariel, Neama, author; Graff, Gregory D., advisor; Davies, Stephen, advisor; Stanelle, James, committee member; Ojima, Dennis, committee member (Colorado State University. Libraries, 2015)
Globally, agriculture has met the needs of a growing population remarkably well (Agriculture and Natural Resources Team of the UK DFID, 2004). However, this success has been at the expense of our natural resources. A sustainable approach must lead future agricultural decision-making processes. According to Tilman, Cassman, Matson, and Polasky (2002), the global population is expected to increase by 50% in 2050; this increase in production will affect the environment adversely. There are numerous global challenges associated with creating a sustainable agriculture model. As one of the most arid countries on Earth and one that is just emerging from decades of authoritarian rule, Libya faces several big challenges in order for its agriculture to meet demand in a sustainable manner. Specifically, improvements in Libya’s seed system may be needed to help close the yield gap, reduce negative externalities associated with agricultural production, and facilitate the adaptation of Libyan agriculture to climate change. While there are many factors that contribute to Libya’s apparent current yield gap in wheat and barley, one of its most important agricultural sectors, the lack of availability of appropriate genotypes for each environment serves as the primary factor focused on in this study. The objectives to this research are to understand what varieties farmers currently grow, why they grow those varieties, and how they access the seed for those varieties as well as understanding what constrains farmers’ adoption of new varieties in order to recommend mechanisms of improvement to the seed system in Libya. To achieve sustainability in agriculture, higher yields must be maintained while minimizing environmental impacts, making it increasingly important to understand the Libyan seed system and its users and their access. This research has two primary hypotheses in regards to closing the yield gap: One focuses on the demand side and why farmers are not adopting improved varieties. The other concerns the supply side and questions of who provides wheat and barley seed to farmers, under what arrangements, and where the genetic varieties originate. The preliminary assumption is that Libyan wheat and barley farmers are more likely to use imported seeds than domestic seeds due to the lack of availability of improved local varieties due to the lack of breeding programs in Libya.
Keywords: breeding programs; seed system; yield gap; imported seeds; adopting improved varieties; sustainable agriculture